Synthesis, characterization, thermodynamic and kinetic properties of a new series of dinuclear PtII complexes - Ertürk, Hakan; Puchta, Ralph; van Eldik, Rudi (European Journal of Inorganic Chemistry, 2009)
The dinuclear PtII complexes bis[(1R,2R)-(-)-1,2-diamino- cyclohexane]chloroplatiiium(II)(u-l,8-octanediamine), bis- [(lR,2R)-(-)-l,2- diaminocyclohexane]chloroplatinum(II)(Li-1,10-decanediamine) and bis[(lR,2R)-(-)-1,2-diamino- cyclohexane]chloroplatin(II)[n-l,4-bis(3-pyridyl) buta-l,3-di-yne] were synthesized. Acid-base titrations and concentration and temperature dependent measurements of the reactions with chloride and thiourea were performed to study the influence of the nature of the bridging ligand on the thermodynamic and kinetic properties of the complexes. The reactions with chloride and thiourea were followed under pseudo-first-order conditions by stopped-flow and UV/Vis spectrophotometry. The results indicate that the bridging ligand has an influence on the reactivity and stability of the complexes towards nucleophiles as well as on possible electronic interactions between the two Ptn centres. The experimental results are discussed in reference to structures obtained by DFT (BP86/LACVP*) calculations. © Wiley-VCH Verlag GmbH & Co. KGaA.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Antitumor agents; Kinetics; Platinum